2001
DOI: 10.3904/kjim.2001.16.2.123
|View full text |Cite
|
Sign up to set email alerts
|

HLA Antigens in Malay Patients with Systemic Lupus Erythematosus : Association with Clinical and Autoantibody Expression

Abstract: Background:Studies have shown that certain genes within the major histocompatibility complex predispose to systemic lupus erythematosus (SLE) and may influence clinical and autoantibody expression. Thus, we studied the frequency of HLA-DR, -DQA, -DQB and -DPB alleles in ethnic Malays with SLE to determine the role of these genes in determining disease susceptibility and their association with clinical and immunological manifestations.Methods:Fifty-six Malay SLE patients were enrolled into the study. Demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 36 publications
(45 reference statements)
1
30
6
Order By: Relevance
“…In addition, we found that DRB4*0101101, 0102, 0103, DQB1*05, DRB1*1301-22, DRB3*0101, 0201, 0202, 0203, 0301 and DQB1*0301, 0304 alleles were significantly increased. This different from a previous study which showed an increase in the DRB1*0501 and *0601 alleles only [10].…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…In addition, we found that DRB4*0101101, 0102, 0103, DQB1*05, DRB1*1301-22, DRB3*0101, 0201, 0202, 0203, 0301 and DQB1*0301, 0304 alleles were significantly increased. This different from a previous study which showed an increase in the DRB1*0501 and *0601 alleles only [10].…”
Section: Discussioncontrasting
confidence: 84%
“…In the Japanese and Korean studies, the most common DRB1 allele was *1501 [17]. The increase of DR2 allele frequency in the Malay patient groups has been previously reported [10]. In contrast, no association was found between DR2 allele frequencies and SLE in the Malay patient group in this present study.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Rezaieyazdi et al [10] also reported absence of significant association between DQ6 and severity of disease in their patients. Contrary to our results Malaysians demonstrated significant association of DQB1*0601 with anti-Sm/RNP and with anti-dsDNA [30]. Tunisians showed no significant association of HLA-DQB1*06 with any of the specific antibodies in SLE [21].…”
Section: Discussioncontrasting
confidence: 85%
“…Recently a significant association and increased evidence of direct involvement in the pathogenesis of tissue injury by the anti SS-A/ Ro and SS-B/ La antibodies are reported (Mavragani et al 2000). In SLE multiple loci within the MHC have been implicated in susceptibility like HLA class II alleles, Complement components and TNF loci (Naves et al 1998;Gladman et al 1999;Galeazzi et al 2000;Huang et al 2001;Azizah et al 2001;Shankarkumar et al 2003). HLA DQ1 and DQ2 are also found to be associated with Ro, La, Sm and dsDNA autoantibodies.…”
Section: Discussionmentioning
confidence: 99%